THE CLOZAPINE EFFECT ON BLOOD GLUCOSE LEVELS, LEUKOCYTES AND PLATELETS IN SCHIZOPHRENIC PATIENTS IN THE MENTAL SERVICE UNIT OF BANYUMAS HOSPITAL - Ikhwan Yuda Kusuma (Jurnal Farmasi Sains dan Praktis, 2021)
Schizophrenia is a disorder of strange and disordered thoughts, delusions, hallucinations, inappropriate influences, and disorders of psychosocial functioning. One of the management of schizophrenia therapy is the administration of atypical antipsychotic drugs, namely clozapine. Clozapine is an antagonist of serotonin (5-HT2) and dopamine type 2 (D2) receptors. However, the risk of using clozapine provides a risk of side effects in the form of metabolic syndromes such as impaired blood glucose regulation and disorders of blood elements such as leukocytes and platelets. This study aims to determine the effect of using clozapine on blood glucose, leukocyte, and platelet levels in schizophrenia patients at Banyumas General Hospital. This research method was carried out by cross-sectional study in outpatient schizophrenia at Banyumas General Hospital who received clozapine therapy and had met the inclusion and exclusion criteria, taken by consecutive sampling, then examined blood glucose levels, leukocyte counts, and platelet counts before and after giving clozapine therapy. Samples were taken on day 1 and day 10 of drug use. Paired t-test statistical analysis was used to see the effect of using clozapine on glucose, leucocyte, and platelet levels. In the T-test, it was found that there was a relationship between the use of clozapine on the patient's blood glucose levels, the use of clozapine did not have a significant effect on the increase in leukocyte levels and there was also a relationship between the use of clozapine and the patient's platelet levels. The results showed that the patient had an increase in blood glucose levels by a percentage (100%), the patient had leukopenia by a percentage (63.5%), the patient had thrombocytopenia by a percentage (75%), while the other patients had thrombocytosis. Patients with hyperglycemia, leucopenia, and thrombocytopenia were those who used clozapine> 12 months